INTERHOSPITAL TRANSPORT OF THE HIGH-RISK NEWBORN: A CHALLENGE FOR THE NURSING STAFF - Paula Cristina de Oliveira Pimenta; Valdecyr Herdy Alves (Universidade Federal do Paraná, 2016)
This study aimed to investigate the conditions in which the interhospital transport of high-risk newborns takes place, between their municipality of origin and the Mother and Child Hospital in Belo Horizonte, in the Brazilian State of Minas Gerais. It is an exploratory and descriptive study undertaken with 35 nursing professionals who are members of the neonatal transportteam, between 1st November 2014 and 30th July 2015. It was evidenced that the interhospital transport of at-risk newborns occurs frequently, from the interior of the State of Minas Gerais to Belo Horizonte, confirming that the municipalities identified lack the human and/or material resources to assist them appropriately, which is considered serious due to the possibility of promoting the worsening of the patient's clinical condition. It is recommended to the municipalities' managers that they should be alert to the necessary conditions required for the transport, so as to minimize adverse events during the journey and so that the newborn may be assisted with quality and safety.